SOSTENIBILIDAD Y DESEMPEÑO AGROECOLÓGICO EN PEQUEÑAS FINCAS DE LA PARROQUIA EL PROGRESO DE LAS ISLAS GALÁPAGOS- ECUADOR. - Sánchez Torres, Adrian Rodolfo (2023)
This study assessed sustainability and agroecological performance in small farms in the El Progreso parish of the Galapagos Islands, Ecuador. Snowball sampling was employed, involving 30 household heads. Data collection utilized the SAFA and TAPE methodologies by the FAO, facilitated by Kobotoolbox. Data processing was conducted using SAFA 3.0 and Excel. The results reveal that small farms in this region exhibit a moderate performance in sustainability (SAFA). Social well-being achieved the highest performance, with a score of 3.47, while environmental integrity showed the lowest performance, scoring 2.52. The primary challenge in agroecological performance (TAPE) lies in the environmental dimension (1.92). Furthermore, the social and cultural dimension exhibited limitations in co-creation and knowledge exchange (1.75), despite a moderate performance in human and social values (2.48). From an economic perspective, farms excel in circular and solidarity economy (3.19), suggesting an orientation toward sustainable and collaborative practices. However, resilience demonstrated only moderate performance, scoring 2.33. The dimensions of nutrition and health (2.56) and governance (2.11) also displayed moderate performances, indicating areas with room for improvement. In conclusion, assessing the sustainability of small farms in the Galapagos Islands is crucial for identifying areas of improvement and developing strategies to promote sustainability. The recommendations derived from this study have the potential to assist these farms in enhancing their sustainability, thereby contributing to environmental conservation and the sustainable development of the Galapagos Islands.